ENSO sentinels in the Americas' humid tropics: We need combined hydrometric and isotopic monitoring for improved El Niño and La Niña impact prediction - Sánchez Murillo, Ricardo (2023)
This Scientific Briefing presents results from a nearly 10-year hydrometric and iso tope monitoring network across north-central Costa Rica, a region known as a headwater-dependent system. This monitoring system has recorded different El Niño and La Niña events and the direct/indirect effects of several hurricane and tropical storm passages. Our results show that El Niño-Southern Oscillation (ENSO) exerts a significant but predictable impact on rainfall amount anomalies, groundwater level and spring discharge, as evidenced by second-order water isotope parameters (e.g., line conditioned-excess or line-conditioned (LC)-excess). Sea surface tempera ture anomaly (El Niño Region 3) is correlated with a reduction in mean annual and cold front rainfall across the headwaters of north-central Costa Rica. During El Niño conditions, rainfall is substantially reduced (up to 69.2%) during the critical cold fronts period, limiting groundwater recharge and promoting an early onset of minimum baseflow conditions (up to 5 months). In contrast, La Niña is associated with increased rainfall and groundwater recharge (up to 94.7% during active cold front periods). During La Niña, the long-term mean spring discharge (39 Ls-1) is exceeded 63–80% of the time, whereas, during El Niño, the exceedance time ranges between 26% and 44%. The regional hydroclimatic variability is also imprinted on the hydrogen and oxygen isotopic compositions of meteoric waters. Drier conditions favoured lower LC-excess in rainfall (-17.3‰) and spring water (-6.5‰), whereas wetter conditions resulted in greater values (rainfall = +17.5‰; spring water = +10.7‰). The lower and higher LC-excess values in rainfall corresponded to the very strong 2014–2016 El Niño and 2018 La Niña, respectively. During the recent triple-dip 2021–23 La Niña, LC-excess exhibited a significant and consistently increasing trend. These findings highlight the importance of combining hydrometric, synoptic and isotopic monitoring as ENSO sentinels to advance our current understanding of ENSO impacts on hydrological systems across the humid Tropics. Such information is critical to constraining the 21st century projections of future water stress across this fragile region.